Differential type I and type III interferon expression profiles in rheumatoid and juvenile idiopathic arthritis - Malik, Anikó E.; Slauenwhite, Drew; McAlpine, Sarah M.; Hanly, John G.; Marshall, Jean S.; Dérfalvi, Beáta; Issekutz, Thomas B. (Frontiers in Medicine, 2024)
Background The role of type I and type III interferons (IFNs) in rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA) is still poorly understood. The objective of this study was to examine the hypothesis that IFN expression profiles differ between subsets of arthritic subjects. Multiple type I and type III IFNs were examined in patients with RA and JIA, as well as among subtypes of JIA. Methods Treatment-naïve RA and JIA patients were enrolled. Droplet-digital PCR was used to measure the expression of type I, II, and III interferons in blood and synovial fluid leukocytes. Dendritic-cell subsets were isolated from synovial fluid to examine IFN expression in each subset. Additionally, synovial mononuclear cells and JIA-derived fibroblast-like synoviocytes were stimulated with TNF, IFNγ, and poly(I:C) to examine inducible IFN-expression. The predominant type I IFN gene expressed by blood leukocytes was IFNκ and was significantly lower in RA than JIA and controls. Oligoarticular and psoriatic JIA subgroups showed higher IFNκ expression than polyarticular JIA and RA. JIA synovial fluid leukocytes expressed abundant IFNγ and type III IFNs (IFNλ1, IFNλ3), with distinct dendritic cell subset contributions. JIA fibroblast-like synoviocytes produced IFNβ, IFNλ1, and IFNλ2 mRNA upon poly(I:C) stimulation.This study revealed differences in IFN expression patterns in RA and JIA, with notable differences between JIA subtypes. The expression levels of IFNκ, IFNγ, IFNλ1 and IFNλ3 in JIA suggest specific roles in disease pathology, influenced by disease subtype and joint microenvironment. This study contributes to understanding IFN-mediated mechanisms in arthritis, potentially guiding targeted therapeutic strategies.